Climate change and biodiversity in Australia: a systematic modelling approach to nationwide species distributions. Issue 2 (3rd April 2019) - Graham, Erin M.; Reside, April E.; Atkinson, Ian; Baird, Daniel; Hodgson, Lauren; James, Cassandra S.; VanDerWal, Jeremy J.
ABSTRACT: Climate change is a driving force of changes to biodiversity worldwide and presents considerable management challenges for the resource-constrained environmental management sector. Effective management of biodiversity requires information about what species are present, how species respond to environmental conditions and which species are likely to be able to persist in the presence of ongoing change. Species distribution models are commonly used to predict future suitable habitat for particular species and areas of interest but a consistent nationwide approach is needed to understand how climate change will affect Australia's biodiversity. Here we describe a modelling approach that uses a consistent workflow and expert vetting to create current and future species distributions for 1872 terrestrial and freshwater vertebrate species. We used two emission scenarios, 18 General Circulation Models and seven time points into the future to explore how individual species distributions and taxa richness in Australia are predicted to change due to climate change. The maps are publicly available online and stakeholders can download them for post hoc analyses to assist in both regional and national management and protection of biodiversity assets and conservation planning for the future.